(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
BardetBiedl syndrome (BBS) is a rare autosomal recessive ciliopathic human genetic disorder characterized by retinal dystrophy, truncal obesity, post-axial polydactyly, renal dysfunction, learning difficulties and hypogonadism. Many associated minor features can be helpful in making a diagnosis and are important in the clinical management of BBS. The diagnosis is based on clinical findings and can be confirmed by sequencing of known disease-causing genes in 80% of patients. BBS genes encode proteins that localize to the cilia and basal body and are involved in cilia biogenesis and function. Mutations lead to defective cilia accounting in part for the pleiotropic effects observed in BBS. We have presented a 11 years old female patient exhibiting characteristic features of Bardet Biedl syndrome (BBS) and then the literature is reviewed. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 67-69